Clinical use of deep speech parameters derived from the semantic verbal fluency task. (31st December 2021) - ter Huurne, Daphne BG; Ramakers, Inez HGB; Linz, Nicklas; König, Alexandra; Langel, Kai; Lindsay, Hali; Verhey, Frans RJ; de Vugt, Marjolein
Abstract: Background: Previous research showed that semantic memory is a good indicator for cognitive decline in early phases of Alzheimer's disease. Automatically derived deep speech parameters from the semantic verbal fluency (SVF) can potentially have an additional value to differentiate SCI, MCI and dementia, compared to the total fluency score. However, the added diagnostic value of (specific) deep speech parameters to the commonly clinically used SVF raw score remains unknown. In the Deepspa project, we investigated the (additional) value of automatically derived speech parameters in clinical practice. We also investigated the relation between automatically derived speech parameters of the SVF and other cognitive tasks, as well as disease severity and functioning in daily living. Method: In the DeepSPA project, 140 participants were recruited from the memory clinic of the MUMC+ (SCI, MCI, ADD). All subjects underwent a cognitive assessment including the SVF. The SVF (animals, 60 seconds) was administered by use of the Delta application (ki elements). Disease severity and functioning in daily life were administered by the Clinical Dementia Rating Scale (CDR) and Disability Assessment for Dementia (DAD) respectively. The agreement between the automatic and clinical raw score of the SVF was assessed by the interclass correlation coefficient. The relation between the deep speech parameters, such as mean word frequency, temporal and semantic clusters, transition time between words etc., and syndrome diagnosis, DAD and CDR were investigated using stepwise regression analyses, corrected for age, education level and gender. Result: Preliminary results showed that deep speech parameters have an additional value in the classification of clinical diagnosis, and disease severity. More specifically, mean word frequency and the mean time between temporal clusters had an added value. The reliability between word count by the application and the clinician was good (ICC=.882, 95% CI = .820‐.923). Results about the relation between deep speech parameters and other cognitive performances will be available at the conference. Conclusion: First results suggest that deep speech parameters have an additional value in the early diagnostics of cognitive impairments. More information about the value of these non‐invasive automatically derived deep speech parameters could improve diagnostic accuracy in clinical practice.